2014 Social Accounting Matrix for Yemen - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This new regional SAM for Yemen includes 57 productive sectors – including 20 agricultural, 25 industrial, and 12 services activities – in four subnational regions: Highlands, Tihama, Aden, and Hadramaut. The regional SAM has 10 factors of production. Labor is differentiated by three educational levels and between the public and private sectors. Capital is disaggregated into four types: crops; livestock; mining; and other. Additionally, the new SAM has 60 representative households. Households were split according to per capita expenditure into five quintiles by rural farm, rural non-farm, and urban areas. These 15 household groups then were differentiated across the four subnational regions. The regionalization of the Yemen SAM for the year 2014 was done for sectoral production, i.e., agriculture, industry, and services; factor markets; and household groups. All of the other accounts in the SAM are at the national level. In total, the regional SAM for Yemen incorporates 379 rows x 379 columns.